1988
DOI: 10.1126/science.3175662
|View full text |Cite
|
Sign up to set email alerts
|

MyoD1: A Nuclear Phosphoprotein Requiring a Myc Homology Region to Convert Fibroblasts to Myoblasts

Abstract: Expression of a complementary DNA (cDNA) encoding the mouse MyoD1 protein in a variety of fibroblast and adipoblast cell lines converts them to myogenic cells. Polyclonal antisera to fusion proteins containing the MyoD1 sequence show that MyoD1 is a phosphoprotein present in the nuclei of proliferating myoblasts and differentiated myotubes but not expressed in 10T1/2 fibroblasts or other nonmuscle cell types. Functional domains of the MyoD1 protein were analyzed by site-directed deletional mutagenesis of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
550
3
6

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 813 publications
(577 citation statements)
references
References 21 publications
(17 reference statements)
13
550
3
6
Order By: Relevance
“…Nuclei reacting with the anti-PCNA, or subsequently with the anti-myogenin, were almost completely eliminated (data not shown). We also demonstrated that exposure of fiber cultures to 5-bromo-2-deoxyuridine (50 μM), a drug which was shown to prevent differentiation of myoblasts in mass culture upon continuous incorporation into the DNA (Stockdale et al, 1964;Tapscott et al, 1988), drastically reduced the numbers of MyoD+ nuclei and extinguished myogenin+ nuclei; no effect was observed on the appearance and disappearance of PCNA+ cells on the fibers. Collectively, the above described experiments which have indicated that there is a link between DNA replication and expression of MyoD and myogenin provide further support that the two myogenic regulatory factor proteins are expressed in cells during or subsequent to their proliferation and not in myonuclei.…”
Section: Quantification Of Satellite Cells On Isolated Fibers Maintaimentioning
confidence: 87%
See 2 more Smart Citations
“…Nuclei reacting with the anti-PCNA, or subsequently with the anti-myogenin, were almost completely eliminated (data not shown). We also demonstrated that exposure of fiber cultures to 5-bromo-2-deoxyuridine (50 μM), a drug which was shown to prevent differentiation of myoblasts in mass culture upon continuous incorporation into the DNA (Stockdale et al, 1964;Tapscott et al, 1988), drastically reduced the numbers of MyoD+ nuclei and extinguished myogenin+ nuclei; no effect was observed on the appearance and disappearance of PCNA+ cells on the fibers. Collectively, the above described experiments which have indicated that there is a link between DNA replication and expression of MyoD and myogenin provide further support that the two myogenic regulatory factor proteins are expressed in cells during or subsequent to their proliferation and not in myonuclei.…”
Section: Quantification Of Satellite Cells On Isolated Fibers Maintaimentioning
confidence: 87%
“…The similarity in the temporal appearance and disappearance of PCNA+ and MyoD+ cells on intact fibers (with or without bFGF) suggests that it is the proliferating satellite cells which express the myogenic regulatory factor protein MyoD. Analyzing the myogenic cell line C2, Tapscott et al (1988) concluded that MyoD protein was expressed by proliferating myoblasts, but not all proliferating myoblasts expressed MyoD. We also monitored the reactivity of mass cultures of rat satellite cells dissociated from isolated fibers and of C2 cells with the antibody against MyoD used in the present fiber study.…”
Section: Patterns Of Pcna Myod Myogenin αSmactin and Devmyosin Prmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount or conformation of MyoD needed to activate genes in muscle fibers and satellite cells may thus be different. MyoD can be phosphorylated (Tapscott et al, 1988) and form heterodimers with other regulatory factors (Farmer et al, 1992): this illustrates the plausibility of MyoD being able to activate different genes in different cellular environments. Second, we believe that the level of MyoD protein in fibers decreases with age and that non-growing innervated fibers contain insignificant levels of MyoD protein.…”
Section: Myod Expression In Fiber Nucleimentioning
confidence: 99%
“…Different HLH transcription factors potentially interact with each other by forming heterodimers [3]. The HLH transcription factors which form heterodimers are grouped into four classes: class A includes MEI (HEB, REB, HTF4), ME2 (ITF2), and E2A which are expressed ubiquitously [3 10]; class B includes cell type and tissue specific proteins such as NSCL, NEX, MASH-l, MASH-2, MyoD and others [11,14]; HES-family includes negatively acting transcriptional regulators HES-1, HES-2, HES-3, HES-5 [15 18]; and Id-like family includes transcriptional regulators lacking the basic, DNA binding domain such as Idl, Id2, Id3, and Id4 [19][20][21][22]. The activity of each individual HLH transcription factor depends on the complexes formed, and how these complexes bind to DNA and interact with the basic transcriptional complex.…”
Section: Introductionmentioning
confidence: 99%